Regional Autonomy and Poverty in Indonesia: A Literature Review - Awal Nopriyanto Bahasoan; Muhammad; Marsudi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the impact of regional autonomy policies on poverty in Indonesia. This study uses the literature review research method which is a very appropriate method used in articles related to regional autonomy and poverty in Indonesia. This is because this method can assist in obtaining a more comprehensive understanding of the concept of regional autonomy and poverty, including theories, concepts and research results related to the topic of regional autonomy and poverty. The results of this study are that regional autonomy has the potential to reduce poverty in Indonesia, especially through improving public services and economic opportunities for people at the local level. However, the successful implementation of the regional autonomy policy in reducing poverty in Indonesia still depends on factors such as the quality of human resources, the availability of financial and technological resources, and an effective governance system. In implementing regional autonomy to reduce poverty.